STUDI KOMPARASI SOAL BERBASIS KEMAMPUAN KONEKSI MATEMATIKA PADA BUKU TEKS SMA KELAS X KURIKULUM 2013 DAN KURIKULUM MERDEKA - Fitra Dewi Istiqomah; Dyana Wijayanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematical connection skills are essential competencies that enable students to integrate various mathematical ideas, both internally and in external applications. This study aims to conduct a comparative study of the content of questions based on mathematical connection skills in the 2013 Curriculum (2017 Revised Edition) and the Independent Curriculum (2023 Revised Edition) for Grade X High School Textbooks. The research method used is descriptive quantitative with a content analysis approach to 350 questions. The analysis instrument refers to the NCTM (2000) standard, which has been used in Arina Susanty's 2018 research which includes: (1) connections between topics in mathematics, (2) connections between mathematics and other fields of science, and (3) connections between mathematics and everyday life, with an in-depth analysis of internal connection sub-indicators using the Hatisaru (2023) taxonomy. The analysis results show that there is a very significant difference in proportion between the two curricula, as strengthened by the Chi-Square test with a value of (2) = 26.554 and a significance value of p = <0,001 (p < 0.05). The 2013 Curriculum Textbook is dominated by connections between topics in mathematics by 77.5%, but has limitations in connections between mathematics and other fields of science and everyday life. In contrast, the Merdeka Curriculum Textbook shows a strengthening of connections between mathematics and everyday life by 26.7%. This indicates that the curriculum transition has brought about a change in the orientation of questions to be more applicable.